2021
DOI: 10.3390/min11020178
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Coloured Gemstones by X-ray Micro Computed Tomography

Abstract: The monetary value of gemstones is based on five variables: rarity, cut, weight, color and clarity. The latter refers to internal impurities and defects. Fashion may also dictate demand and price. To enhance some of these features and value, gemstones are treated. Disclosure or nondisclosure thereof has been controversial and affected consumer confidence. Most of these treatments are difficult to detect with the naked eye and accurately quantify with traditional optical and analytical methods. X-ray micro comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Their results showed that HRXCT is a promising tool for the non-destructive characterization of fluid and melt inclusions. Heyn et al performed the X-ray CT on several gemstone varieties, including corundum, topaz, and quartz [23].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that HRXCT is a promising tool for the non-destructive characterization of fluid and melt inclusions. Heyn et al performed the X-ray CT on several gemstone varieties, including corundum, topaz, and quartz [23].…”
Section: Introductionmentioning
confidence: 99%